Intensity of human prion disease surveillance predicts observed disease incidence. Issue 12 (21st August 2013) - Klug, Genevieve M J A; Wand, Handan; Simpson, Marion; Boyd, Alison; Law, Matthew; Masters, Colin L; Matěj, Radoslav; Howley, Rachel; Farrell, Michael; Breithaupt, Maren; Zerr, Inga; van Duijn, Cornelia; et al.
Abstract : Background: Prospective national screening and surveillance programmes serve a range of public health functions. Objectively determining their adequacy and impact on disease may be problematic for rare disorders. We undertook to assess whether objective measures of disease surveillance intensity could be developed for the rare disorder sporadic Creutzfeldt–Jakob disease (CJD) and whether such measures correlate with disease incidence. Method: From 10 countries with national human prion disease surveillance centres, the annual number of suspected prion disease cases notified to each national unit (n=17 610), referrals for cerebrospinal fluid (CSF) 14-3-3 protein diagnostic testing (n=28 780) and the number of suspect cases undergoing diagnostic neuropathological examination (n=4885) from 1993 to 2006 were collected. Age and survey year adjusted incidence rate ratios with 95% CIs were estimated using Poisson regression models to assess risk factors for sporadic, non-sporadic and all prion disease cases. Results: Age and survey year adjusted analysis showed all three surveillance intensity measures (suspected human prion disease notifications, 14-3-3 protein diagnostic test referrals and neuropathological examinations of suspect cases) significantly predicted the incidence of sporadic CJD, non-sporadic CJD and all prion disease. Conclusions: Routine national surveillance methods adjusted as population rates allow objective determination of surveillance intensity, which correlates positively with reported incidence for human prion disease, especially sporadic CJD, largely independent of national context. The predictive relationship between surveillance intensity and disease incidence should facilitate more rapid delineation of aberrations in disease occurrence and assessment of the adequacy of disease monitoring by national registries.